2022
DOI: 10.1002/cam4.4937
|View full text |Cite
|
Sign up to set email alerts
|

Idarubicin‐Loaded DEB‐TACE plus Lenvatinib versus Lenvatinib for patients with advanced hepatocellular carcinoma: A propensity score‐matching analysis

Abstract: Aims To investigate the efficacy and safety of lenvatinib and idarubicin‐loaded drug‐eluting beads transarterial chemoembolization (IDADEB‐TACE) in primary advanced hepatocellular carcinoma (HCC). Methods This retrospective study included patients with primary advanced HCC who received either lenvatinib monotherapy or lenvatinib plus IDADEB‐TACE as first‐line treatment from September 2019 to September 2020 at three institutes. Overall survival (OS), time to progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
(80 reference statements)
0
7
0
1
Order By: Relevance
“…In retrospektiven Studien bei Patienten (vorweigend aus dem asiatischen Raum und HBV) mit fortgeschrittenem Stadium BCLC B und bei Patienten mit Stadium BCLC C (mit Pfortaderinvasion und/oder extrahepatischer Metastasierung) bei denen eine Indikation zur TACE gestellt wird, konnte das progressionsfreies Überleben und Gesamtüberleben verlängert werden, wenn die TACE mit einer Systemtherapie mit Lenvatinib und PD-1-Inhibitor kombiniert wird [396][397][398][399][400].…”
Section: Kombination Von Systemtherapie Mit Lokoregionärer Therapieunclassified
“…In retrospektiven Studien bei Patienten (vorweigend aus dem asiatischen Raum und HBV) mit fortgeschrittenem Stadium BCLC B und bei Patienten mit Stadium BCLC C (mit Pfortaderinvasion und/oder extrahepatischer Metastasierung) bei denen eine Indikation zur TACE gestellt wird, konnte das progressionsfreies Überleben und Gesamtüberleben verlängert werden, wenn die TACE mit einer Systemtherapie mit Lenvatinib und PD-1-Inhibitor kombiniert wird [396][397][398][399][400].…”
Section: Kombination Von Systemtherapie Mit Lokoregionärer Therapieunclassified
“…A total of 573 articles were retrieved, and 244 repeated articles were excluded by title, year of publication, and author information. Then after reading abstracts and full-text screening, 311 articles that did not meet the criteria were excluded and finally included 18 studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Fig. 1).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Ten studies [9][10][11][12][13][14][15][16]18,25] provided 6-month OS rate data, of which 5 studies [9,11,14,18,25] were TACE plus lenvatinib versus TACE alone, and the other 5 studies [10,12,13,15,16] were TACE plus lenvatinib versus lenvatinib alone. Based on the heterogeneity test results (P = .95, I 2 = 0%; P = .52, I 2 = 0%).…”
Section: Os Ratementioning
confidence: 99%
See 1 more Smart Citation
“…4,20 Previous studies have evaluated lenvatinib plus TACE (Len-TACE) in patients with advanced/unresectable HCC and showed superior treatment efficacy of the combination versus lenvatinib or TACE alone. 7,[22][23][24] More recently, we conducted a retrospective study and found that the combination of lenvatinib, PD-1 inhibitor and TACE conferred improved tumour control and survival benefit in patients with advanced stage HCC, implying that the triple therapy might bring a synergistic antitumour effect for HCC. 6 Herein, we present the results of a single-arm phase II study which explored the efficacy and safety of lenvatinib, sintilimab (a PD-1 inhibitor) plus TACE (Len-Sin-TACE) as the first-line treatment for advanced stage HCC.…”
Section: Introductionmentioning
confidence: 99%